Dampak Media Promosi Kesehatan terhadap Peningkatan Pengetahuan Mahasiswa Tentang Bahaya Merokok - Sitti Nurhidayanti Ishak (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: Smoking behavior is a fundamental problem in many countries, including Indonesia. This is exacerbated by the absence of strict regulations regarding the sale of cigarettes, so it is easy for a teenager to get cigarettes because they are sold freely. For this reason, it is necessary to take preventive steps to overcome this problem.Objective: This study aims to see the role of health promotion media through videos and leaflets on increasing students' knowledge about the dangers of smoking.Methods: This study used a simple experimental method involving 30 samples of students who were divided into a control group and an intervention group. Hypothesis testing using Paired Sample T-Test to see the difference before and after being given the intervention and using Independent Sample T-Test to see the difference between the control group and the intervention group.Results: The results of this study indicate an increase in student knowledge about the dangers of smoking from before being given literacy and after being given literacy through video media and leaflets. The changes were not significant in the control group who were not given literacy about the dangers of smoking.Conclusion: These results can be used as a reference for health facilities and the government in taking preventive steps to prevent the use of cigarettes in adolescents.